Combined methods of teaching foreign students - Solovyova, O. V.; Соловйова, Ольга Володимирівна (Харків : ХНАДУ, 2023)
Modern higher education is being rapidly filled with new means of information technologies, which leads to a change in the ways of providing new material using all available modern educational methods in the conditions of online and off-line learning.
Keywords: тези доповідей